The Degree of Knowledge and Use of Authentic Assessment Tools by Basic Elementary Teachers' According to some Variables: أمجد عزات جمعة، شريف عبد الرحمن السعودي، و سلمى علي العلوي (Journal of the College of Education for Women, 2021)
Evaluation is one of the most important elements of teaching process. The recent trends in evaluation and educational reform movements have called for using alternative evaluation, which focuses on performance evaluation. Authentic assessment is usually described as formative, in which students participate in their acquisition, in addition to the fact that students are productive and active, which is reflected in the students' achievement and skill level. The study aims to reveal the degree of knowledge and use of alternative assessment tools by primary school teachers in Gaza -Palestine. To meet the objective of the study, the researchers used the descriptive-analytical method and the questioner as a study tool. The study sample consisted of (134) elementary basic school teachers in the Gaza governorate in Palestine. Results have shown that the percentage of knowledge of alternative evaluation tools reached (77.7%), which is a high level, and that the percentage of using alternative evaluation tools reached (70.3%). As it is seen, the percentages do not vary according to variables, such as: gender, educational qualification, specialization, classes taught by the teacher, years of service, type of school, gender of school students, educational region, and taking training courses. Howerver, the degree of usage of such alternative tools varies in favour of basic education. The study recommends continuing to motivate primary school teachers to employ alternative assessment tools, and to support them with courses and workshops that enhance their skills in employing these tools